Determination of maternal, neonatal and infant mortality in Khotang, Panchthar, Taplejung and Terhathum districts. - Joshi,Anand Ballabh (2017)
SUMMARY: Background and Objective: Although Nepal has achieved progress in reducing maternal, neonatal and infant deaths over the years, more need to be done to improve attributing factors including access to health facilities, utilization of maternal and neonatal health services, institutional delivery, and socio-economic status. In the absence of comprehensive registration of deaths and causes of deaths, the accurate measure of maternal, infant and neonatal deaths are difficult. Therefore, the objective of this study was to determine maternal mortality ratio, neonatal and infant mortality rate in Khotang, Panchthar, Taplejung and Terhathum districts. Methods: A retrospective study was conducted to enumerate maternal, neonatal, and infant deaths on the past three years preceding the survey. The survey team prepared the list of the health facilities to be covered for survey with the help of District Health Office. A team of research assistants organized a meeting with health workers of the health facility, FCHVs, teachers, local leaders and religious leaders, traditional healers, traditional birth attendants in a health facility. In a meeting, the survey team enlisted all deaths of women aged 15-49 years and neonatal and infant death events of the district retrospectively within last three years, July 15, 2013 to July 15, 2016. The team covered all wards of the VDC (the coverage area of health facility) to collect information of death events. The identified/reported death cases were listed with all the basic information. Then the deaths were validated by the survey team as maternal, neonatal and infant deaths at the household level. The survey team visited each household with deaths as reported by key informants in the meeting along with FCHV of respective ward. During validation, household head and husband/father/mother of the deceased were interviewed. Findings: Neonatal mortality rates per 1000 live births in FY 2072/073 were 19.29 in Khotang, 28.81 in Taplejung, 13.77 in Panchthar and 21.13 in Terhathum. Infant mortality rates per 1000 live births in FY 2072/073 were 28.35 in Khotang, 38.31 in Taplejung, 19.09 in Panchthar and 24.09 in Terhathum. In total 748 infant deaths in four districts, 68.7% were delivered at home and 31.3% were delivered at health facility. Among total 748 infant deaths in four districts, 426 (57.0%) deaths were during early neonatal period (within 7 days of birth) and, 75.9% infant deaths were in neonatal period. Perinatal asphyxia (24.9%), neonatal sepsis (16.6%), pneumonia (12.6%), prematurity and complications (12.3%), sepsis (8.6%), and low birth weight with complications (5.1%) were the most common causes of neonatal/infant deaths. In FY 2072/073, MMR per 100,000 live births was 237 in Taplejung, 127 in Terhathum, 116 in Khotang and 90 in Panchthar. Among total maternal deaths, 24 (46.2%) deaths were during child birth, 22 (42.3%) deaths were within post partum period and 6 (11.5%) deaths were during pregnancy. Regarding place of maternal deaths, 31 (59.6%) deaths took place on the way to hospital. Similarly, 11 (21.2%) maternal deaths occurred at health facility and 10 (19.2%) maternal deaths occurred at home. Among maternal deaths, 30 (57.7%) were due to post partum haemorrhage, 4 (7.7%) were due to obstructed labour, 3 (5.8%) were due to pre-eclampsia and 3 (5.8%) were due to eclampsia. Conclusions: The district health system should be strengthened for proper surveillance and reporting of death events including from the community since there are many deaths outside of the health facilities. Post partum haemorrhage, obstructed labour, pre-eclampsia and eclampsia targeted response activities should be available in health facilities for reducing maternal deaths. It is important to decrease patient delay including decision making for seeking care. Every delivery should be attended by skilled birth attendant. Neonatal/infants death prevention activities should address birth asphyxia, neonatal sepsis, still birth, pneumonia, prematurity and complications, sepsis and low birth weight with complications. Capacity of different level health workers should be strengthened to response timely and provide quality of maternal and neonatal care in respective areas.